2014
DOI: 10.1097/spv.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Robotic Sacrocolpopexy

Abstract: Objectives Robotic sacrocolpopexy has been rapidly incorporated into surgical practice without comprehensive and systematically published outcome data. The aim of this study was to systematically review the current published peer-reviewed literature on robotic-assisted laparoscopic sacrocolpopexy with greater than six-month anatomic outcome data. Methods Studies were selected after applying predetermined inclusion and exclusion criteria to a MEDLINE search. Two independent reviewers blinded to each other’s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In our study, preoperative and postoperative POP-Q measurements predictably improved following surgical intervention, regardless of cohort. Our findings are consistent with a meta-analysis by Hudson et al ( 27 ), who observed an overall anatomical success rate of 98.6% ( 27 ). However, the mean follow-up from this meta-analysis was 26.9±17.3 months as compared to our study that used a relatively short 12-week follow-up period.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, preoperative and postoperative POP-Q measurements predictably improved following surgical intervention, regardless of cohort. Our findings are consistent with a meta-analysis by Hudson et al ( 27 ), who observed an overall anatomical success rate of 98.6% ( 27 ). However, the mean follow-up from this meta-analysis was 26.9±17.3 months as compared to our study that used a relatively short 12-week follow-up period.…”
Section: Discussionsupporting
confidence: 93%
“…13 Other studies, too, have shown improvement in QOL scores using the PFDI and the PFIQ. 1418 In a recently published study by Jong and colleagues, following robotic mesh sacrocolpopexy of 56 women with a mean follow-up time of 3 years, mean AUA QOL score improved significantly from a mean of 4–1.78 postoperatively. However, the mean UDI-6 score did not improve to a level of statistical significance (5–4.59, p = 0.40).…”
Section: Discussionmentioning
confidence: 97%
“…Our concomitant rectocele repair rate of 24.4% is slightly higher than those reported in a 2014 meta-analysis of 13 studies, showing that 18.5% of patients have a rectocele repair at the time of robotic sacrocolpopexy. 15 However, in a Paraiso’s cohort of 40 robotic sacrocolpopexy cases, rectocele was performed in 29% of patients. 17…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to other authors who observed PFDI-20 to be useful in vault prolapse and to see the impact of surgical method including robotic surgery. [ 25 ] It can be seen that surgical treatment of vault prolapse by both vaginal and abdominal routes significantly lowered PFDI-20 and improved the quality of life of patients suffering from vault prolapse with no significant difference in two techniques of vault prolapse surgery.…”
Section: Discussionmentioning
confidence: 99%